Externalities and the Social Return to Education in Indonesia - Purnastuti, Losina; Salim, Ruhul (The Centre for Labour Market Research, Curtin Business School, Curtin University of Technology, 2015)
It is widely known that education provides economic benefits to individuals. However, education also has the potential to generate significant externalities. These external effects of education, in Indonesia, are the focus of the current paper. They are investigated using a local labour market (the province) approach. Significant externalities, as high as, or even much higher than, the private return to schooling, are documented, using both OLS and IV estimations. Sensitivity tests involving separate analyses for skill groups along the lines of Moretti (2004a) and Muravyev (2008), indicate that this finding is robust. The results thus strongly support the view that investing in education is more important for aggregate economic outcomes than it is for the individuals who do so. It appears that there is a clear role for the government fostering further expansion of education opportunities in Indonesia.